INOVASI OLAHAN PMT-P DARI KURMA, HABBATUSAUDA, DAN MINYAK ZAITUN UNTUK BALITA GIZI KURANG - Evi Hasnita; Silvia Suradi (Maternal Child Health Care, 2021)
According to data from the World Health Organization (2020), 45% of children under five suffered from malnutrition. Nutritional problems have an impact on the decline in the quality of human resources resulting in failure of physical growth, mental development and intelligence, decreased productivity, increased morbidity and mortality of children under five. Optimizing the handling of nutritional problems in toddlers can be done through the development of supplementary food formulas by considering aspects of nutrition, health benefits, acceptability and resistance as well as the advantages of local food resources. The purpose of this study was to create an innovation of PMT-P processed from dates, black seed and olive oil, then to test macronutrient levels and organoleptic tests.This study was true experimental research. It was carried out in two places, namely macronutrient testing at the Fishery Products Chemistry Laboratory, Riau University and organoleptic tests on 25 untrained panelists in the working area of Nilam Sari Community Health Center, Bukittinggi City on December 2020 - January 2021. The results of this study indicated that the levels of macronutrients in the innovation of processed PMT-P per chip (10gr) and in the control, namely; carbohydrates 4.1197 g and 1.1322 g, protein 0.7866 g and 0, 1922 g, fat 1.8051 and 0.6784 g. In the organoleptic test, it was found that 52% of panelists chose to like and 36% really liked the smell of cookies, 68% of panelists chose to like and 32% really liked the color of cookies, 44% of panelists chose to like and 48% really liked the taste of cookies, and 44% panelists chose to like and 48% really like the texture of cookies. Keywords :Toddler, PMT-P, Nutritional Status, Macronutrients, Organoleptic Test References : 35 (2012-2020)